Modification of the existing maximum residue levels for fluoxastrobin in oilseeds. (13th August 2018) - ; Brancato, Alba; Brocca, Daniela; Carrasco Cabrera, Luis; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant Arysta LifeSciences SAS submitted a request to the competent national authority in the United Kingdom to modify the existing maximum residue levels (MRL) for the active substance fluoxastrobin in certain oilseeds. The data submitted in support of the request were found to be sufficient to derive MRL proposals for the oilseeds for which a modification was requested. Adequate analytical methods for enforcement are available to control the residues of fluoxastrobin and its Z ‐isomer in the commodities under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the short‐term and long‐term intake of residues resulting from the new intended use of fluoxastrobin according to the reported agricultural practice is unlikely to present a risk to consumer health. The reliable end points, appropriate for use in regulatory risk assessment are presented.